Composite detergents with antibacterial properties based on mixtures of cetylpyridinium chloride with Genapol (Chemical Bulletin of Kazakh National University, 2024)
This study focuses on the properties of the nonionic surfactant Genapol and the cationic surfactant cetylpyridinium chloride (CPC) to develop a composite detergent with bactericidal activity. Research includes studying the properties of CPC and Genapol solutions, creating composite mixtures with different concentration ratios and assessing the bactericidal effectiveness of the resulting detergents.The main foaming agents CPC and Genapol were used without purification, which emphasizes their high biodegradability. Various tests, including surface tension measurements, contact angle evaluation and pH measurements, were carried out at room temperature to evaluate the properties of surfactants and surfactant mixtures.The results show that CPC exhibits foaming, emulsifying and bactericidal properties due to its high surface activity and adsorption capacity. Genapol has the advantages of high surface activity at different pH levels, excellent foaming and emulsifying properties. The combination of these surfactants in a complex detergent creates a universal cleaner with antibacterial properties independent of pH and environmental harshness. The bactericidal effect of solutions of CPC Genapol mixtures was also determined.The results show that the composite solution exhibits a noticeable bactericidal effect with zones of growth inhibition ranging from 13.5±0.5 mm to 17±0.1 mm. The greatest antibacterial activity was observed against Micobacterium citreum and Bacillus subtilis. Sarcina flava and Staphylococcus aureus showed similar growth inhibition results.
Keywords: surface activity; surfactants; detergents; Genapol; cetylpyridinium chloride; antibacterial activity; zone of inhibition; pathogenic microorganisms